2016
DOI: 10.1590/s0102-05362016003015
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo e uso de variedades crioulas de abóboras ornamentais no Rio Grande do Sul

Abstract: Production and use of ornamental pumpkin landraces in the Rio Grande do Sul State, BrazilLandraces of several cucurbit species are cultivated in Brazil. The greatest genetic diversity of cultivated Cucurbita seems to be found in Rio Grande do Sul State, where farmers have the knowledge and practice to store and exchange these seeds. Many of these varieties have potential for ornamental use. This research was developed to rescue the popular knowledge associated with the use and cultivation of landraces of ornam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…O Banco Ativo de Germoplasma (BAG) de Cucurbitáceas, da Embrapa Clima Temperado, conserva 640 acessos de diferentes espécies cultivadas dos gêneros Citrullus, Cucumis, Cucurbita, Lagenaria, Luffa, Momordica e Sicana, sendo que 85 acessos são variedades crioulas de Cucurbita maxima. Porém, apenas uma pequena parte do acervo total do BAG já foi caracterizada (Neitzke et al, 2009;Priori, 2011;Priori, 2015;Fischer, 2012;Fischer et al, 2015;Fischer et al, 2016;Priori et al, 2012;Priori et al, 2013;Priori, et al, 2017). Para a realização deste trabalho, nove variedades crioulas de C. maxima foram selecionadas, seguindo-se alguns critérios, como a quantidade de sementes disponíveis no BAG e suficientes para a implantação do experimento, os dados de passaporte (como local de coleta, características dos frutos, reveladas pelos agricultores que doaram as sementes, como formato, cor da casca e tamanho dos frutos).…”
Section: Introductionunclassified
“…O Banco Ativo de Germoplasma (BAG) de Cucurbitáceas, da Embrapa Clima Temperado, conserva 640 acessos de diferentes espécies cultivadas dos gêneros Citrullus, Cucumis, Cucurbita, Lagenaria, Luffa, Momordica e Sicana, sendo que 85 acessos são variedades crioulas de Cucurbita maxima. Porém, apenas uma pequena parte do acervo total do BAG já foi caracterizada (Neitzke et al, 2009;Priori, 2011;Priori, 2015;Fischer, 2012;Fischer et al, 2015;Fischer et al, 2016;Priori et al, 2012;Priori et al, 2013;Priori, et al, 2017). Para a realização deste trabalho, nove variedades crioulas de C. maxima foram selecionadas, seguindo-se alguns critérios, como a quantidade de sementes disponíveis no BAG e suficientes para a implantação do experimento, os dados de passaporte (como local de coleta, características dos frutos, reveladas pelos agricultores que doaram as sementes, como formato, cor da casca e tamanho dos frutos).…”
Section: Introductionunclassified
“…The evaluation of plant germplasm through images is potentially a more accurate and faster alternative than traditional techniques. The shape of the fruit has been widely studied (Fischer et al, 2015;Fischer et al, 2016;Priori et al, 2018). This fact demonstrates the relevance in the search for new optimizing alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, researchers have studied the ornamental use of plants traditionally exploited for food, especially those that produce fruits, such as peppers (Neitzke et al, 2010), pumpkins (Boiteux et al, 2007;Fischer et al, 2015;Fischer et al, 2016), pineapples (Souza et al, 2007) and tomatoes (Embrapa, 2014). Despite the recent interest in the research, the ornamental use of fruits has been reported since the period of navigations, when Europeans took the tomato fruit from the Americas to Europe in the 16th century for decorative purposes and later began to explore it as food (Razdan and Mattoo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The ornamental mini-pumpkins (Cucurbita maxima, C. moschata e C. pepo), belong to the Cucurbitaceae family and originate from Americas (Fischer et al, 2016). They are annual plants, with herbaceous stem, prostrate growth habit and provided with tendrils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation